Em defesa da liberdade : libertos e livres de cor nos tribunais do Antigo Regime português (Mariana e Lisboa, 1720-1819) - Pinheiro, Fernanda Aparecida Domingos, 1982- (2013)
Orientador: Silvia Hunold Lara